Latihan Akuatik Meningkatkan Nafsu Makan Anak - Anastasia Martha; Alida Nella Fedelina Rassa (Universitas Negeri Surabaya, 2024)
Background: This study aims to examine how children's hunger is affected by aquatic exercise. The hypothalamus and brainstem are the sites of several peripheral signals that regulate appetite and eating behavior in response to food intake. These feedback signals involve several gut hormones, such as ghrelin, peptide YY (PYY), and glucagon-like peptide-1 (GLP-1). Ghrelin is released several hours after working out in the water, which increases appetite Methods: Using the total sampling approach, a pre-test and post-test design was employed for a set of 29 respondents. For eight weeks, aquatic exercise is done once a week Results: According to the study's findings, children's appetite is influenced by water-based exercise in three ways: with a significance value of 0.000 for their desire to enjoy food, a significance value of 0.046 for their reactions to it, and a significance value of 0.025 for their picky eating habits Conclusions: As a result, playing in the water might make kids more hungry and want to savor every meal. As a result, kids who exercise in the water on a daily basis run a possibility of becoming excessively fed